TEACHER'S READINESS IN TEACHING ENGLISH USING DIGITAL TECHNOLOGY IN SENIOR HIGH SCHOOL MAMUJU - Aulia Mutmainna Bachtiar; Nurdin Noni; Maemuna Muhayyang (Universitas Negeri Makassar, 2022)
The purpose of this study was to determine the readiness of teachers to use digital technology in teaching English. This research is mixed research (quantitative and qualitative) using the explanatory sequential method. The researchers chose 3 Senior High Schools in Mamuju namely, SMAN 1 Mamuju, SMAN 2 Mamuju, and SMAN 3 Mamuju. Data collection techniques used questionnaires and interviews. This study shows that the readiness of digital technology in teaching English is very ready, which can be seen from the three aspects of readiness: emotive attitudinal Readiness, cognitive Readiness, and behavioral Readiness supported by teacher understanding, teacher enthusiasm for using digital technology in teaching, teacher skills, and the availability of media tools. Therefore, the understanding and competence possessed by a teacher about digital technology can be integrated with learning and teaching.